The Effect of Giving Super Red Dragon Fruit (Hylocereus Costarisensis) on Increasing Hemoglobin Levels Preparing for Preconception in Prospective Brides - Nara Lintan Mega Puspita; Huda Rohmawati; Ihrom Fatma S.; Putri Erika; Bintang Dwi Pratiwi (Universitas STRADA Indonesia, 2024)
Anemia is the biggest public health problem in the world, especially for women of childbearing age. Anemia plays a role in increasing the prevalence of maternal mortality and morbidity and for infants it can increase the risk of infant morbidity and mortality as well as LBW. Dragon fruit contains iron, antioxidants and folates in abundance and can help in the formation of red blood cells, preventing anemia and increasing hemoglobin levels. The aim of this is to determine the effect of giving dragon fruit on hemoglobin levels in preparing for preconception in prospective brides and grooms. The design used in this research was pre-experimental one group pretest-posttest design. The population in this study were prospective brides and grooms who experienced anemia at the Ngadiluwih Community Health Center, Kediri Regency. A sample of 16 respondents was taken using an incidental sampling technique. The instruments used were observation sheets, HB, dragon fruit.